Characterization of C-Type Particles Produced by a Tissue Culture-Adapted Murine Myeloma - Volkman, Loy E. (1973)
C-type particles produced by a tissue culture-adapted BALB/c myeloma were characterized. It was determined that although the particles were morphologically and antigenically similar to murine leukemia and sarcoma virus, the size of their RNA was different, they lacked RNA-dependent DNA polymerase, they were unstable in NET buffer, sucrose and citrate but were stable in glycerol and Earle balanced salt solution, and they behaved differently from oncornaviruses when treated with ether and detergent.